The Role of Pregnant Women's Perception and Social Support on the Utilization of VCT Services - Ayik Mirayanti Mandagi; Jayanti Dian Eka Sari; Diansanto Prayoga; Syifa’ul Lailiyah; Vidia Nuria Rahman; Arini Khoirunnisa (Journal of Educational, Health and Community Psychology, 2022)
Voluntary Counseling and Testing (VCT) is an HIV/AIDS prevention program that has high evidence of effectiveness, especially for individuals who have HIV/AIDS risk behaviors. The behavior of using VCT services can be seen from the influence of perceptions and social support. This study has theÂ purpose to analyze the correlation between perceptions and social support of pregnant women with the behavior of using VCT services in Banyuwangi. The method used in this study is an analytical observational with a cross-sectional research design. The population of this study was pregnant women in the Kembiritan, Sobo, Genteng Kulon, Kertosari, Singojuruh, and Singotrunan in the range of May - to November 2018. The sampling technique used was proportional random sampling. Most of the respondents have a bad perception that is 51. 6%. The majority of respondents have poor social support, namely 84.1%. The percentage of respondents who have good perceptions and behaviors in utilizing VCT services is 62.4%. Meanwhile, 60.1% of respondents who have social support and good behavior use VCT.